Effectiveness of a Pedometer-Based Telephone Coaching Program on Weight and Physical Activity for People Referred to a Cardiac Rehabilitation Program: A RANDOMIZED CONTROLLED TRIAL. Issue 2 (March 2015) - Sangster, Janice; Furber, Susan; Allman-Farinelli, Margaret; Phongsavan, Philayrath; Redfern, Julie; Haas, Marion; Church, Jody; Mark, Andy; Bauman, Adrian
Abstract : PURPOSE: To determine the effectiveness of a pedometer-based telephone lifestyle coaching intervention on weight and physical activity. METHODS: A randomized controlled trial was conducted with 313 patients referred to cardiac rehabilitation in rural and urban Australia. Participants were allocated to a healthy weight (HW) (4 telephone coaching sessions on weight and physical activity) or a physical activity (PA) intervention (2 telephone coaching sessions on physical activity). Weight and physical activity were assessed by self-report at baseline, short-term (6-8 weeks), and medium-term (6-8 months). RESULTS: More than 90% of participants completed the trial. Over the medium-term, participants in the HW group decreased their weight compared with participants in the PA group ( P = .005). Participants in the HW group with a body mass index of ≥25 kg/m 2 had a mean weight loss of 1.6 kg compared with participants in the PA-only group who lost a mean of 0.4 kg ( P = .015). Short-term, both groups increased their physical activity time, and the PA group maintained this increase at the medium-term. CONCLUSIONS: Participants in the HW group achieved modest improvements in weight, and those in the PA group demonstrated increased physical activity. Low-contact, telephone-based interventions are a feasible means of delivering lifestyle interventions for underserved rural communities, for those not attending cardiac rehabilitation, or as an adjunct to cardiac rehabilitation. Abstract : A randomized controlled trial was conducted to determine the effectiveness of a pedometer-based telephone coaching intervention, on weight and physical activity, for urban and rural patients referred to cardiac rehabilitation. Healthy weight patients achieved modest improvements in weight, and the physical activity group demonstrated increased physical activity.